FoR Codes pendulum: Publishing choices within Australian research assessment - Bennett, Dawn; Genoni, Paul; Haddow, Gaby (NTEU, 2011)
This paper reports on an exploratory case study that considered the impacts of journal ranking and Fields of Research codes on the publishing decisions of Australian authors. The study also considered the level of alignment between authors’ allocation of Fields of Research codes and the codes assigned to the journals in which they were published. The conclusion is reached that authors are still coming to an understanding of the impact of research assessment on their publishing choices and the process of scholarly communication within their discipline. Findings point to a number of concerns about the impact of both journal ranking and discipline-specific research codes.